MECHANISMS FOR INCREASING THE INDICATORS OF MASTERING THE SUBJECT OF PEDAGOGY IN HIGHER EDUCATION STUDENTS - Erkaboeva Nigora Shermatova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the mechanisms for increasing the indicators of mastering the subject of pedagogy in students of Higher Education.